2019
DOI: 10.1177/2329488419829886
|View full text |Cite
|
Sign up to set email alerts
|

Analyst Following, Country’s Financial Development, and the Selective Use of Graphical Information in Corporate Annual Reports

Abstract: This article investigates whether and how the demand for information at country and firm levels affects the selective use of key performance indicators graphs in corporate annual reports. Our study finds that the country-level and firm-level demands for information provide an incentive, rather than a curb, for a selective display of key performance indicators, which is an important concern in corporate communication and reporting. The external pressure from the demand for information seems to encourage, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
(240 reference statements)
0
4
0
Order By: Relevance
“…In fact, the existing literature has found impression management in Spanish corporate documents (Guillamon-Saorin et al, 2012;Guillamón-Saorín & Martínez-López, 2013). However, it is well known that disclosure is expected to vary between countries, legal systems and other factors (Doupnik & Riccio, 2006;Melis & Aresu, 2022). Most of the existing research on impression management has been developed in Anglophone countries.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In fact, the existing literature has found impression management in Spanish corporate documents (Guillamon-Saorin et al, 2012;Guillamón-Saorín & Martínez-López, 2013). However, it is well known that disclosure is expected to vary between countries, legal systems and other factors (Doupnik & Riccio, 2006;Melis & Aresu, 2022). Most of the existing research on impression management has been developed in Anglophone countries.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another 21 articles (23.1%) focused on the knowledge sources used in business communication practice. Three tackled artificial intelligence resources (Getchell et al, 2022; Naidoo & Dulek, 2022; Salomonson et al, 2013), three assessed the communication of emotions (Casado-Molina et al, 2022; Pickering, 2018; Xu & Wu, 2020), three focused on tasks of information gathering and storage (Craig & Allen, 2013; Gómez & Ballard, 2013; Young, 2018), five on the visualization of data (Jones et al, 2020; Kernbach et al, 2015; Laidroo, 2019; Melis & Aresu, 2022; Toth, 2013), and four on the business uses of personal stories (Yang, 2013) and narrative more generally (Aggerholm, 2014; Laskin, 2018; Rawlins, 2014). Three articles directly address the norms of rational thinking expected in the business environment (Geertshuis et al, 2015; Mandhana, 2022; Simonsson & Heide, 2018).…”
Section: An Analysis Of the Rhetorical Evolution In The Business Comm...mentioning
confidence: 99%
“…Professional uses of implicit forms of reasoning and tacit knowledge are well documented in this selection of articles, including emotional content (Casado-Molina et al, 2022; Pickering, 2018; Xu & Wu, 2020). Important communications are no longer exclusively textual, and many authors addressed the specifics of visual display (Jones et al, 2020; Kernbach et al, 2015; Laidroo, 2019; Melis & Aresu, 2022; Toth, 2013) and narrative structure (Aggerholm, 2014; Laskin, 2018; Rawlins, 2014; Yang, 2013).…”
Section: An Analysis Of the Rhetorical Evolution In The Business Comm...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Beattie and Jones (2000) found that companies are more likely to include graphs of key financial variables when their profit has increased. Melis and Aresu (2019) found "a selective display of key performance indicators, which is an important concern in corporate communication and reporting" and Moreno et al (2019) use of "qualitative textual characteristics with a self-serving bias, but did not use those with a more quantitative character". In prior study's findings are that "92 per cent of profitable companies mentioned at least one key financial variable compared to 86 per cent of unprofitable companies" (Clatworthy & Jones, 2006, p. 503) Н6: The CEO's statements of "good performers" and "poor performers" will contain a similar number of quantitative references.…”
Section: Hypothesis Constructionmentioning
confidence: 99%